Near Real-Time Processing Chain for MSG SEVIRI Data for Free and Immediate Earth Monitoring Capabilities - Sobrino, José A.; Julien, Yves (Frontiers in Remote Sensing, 2021)
Although numerous instruments are continuously observing our planet, the general public has a low access to these data, either being provided with a delay, or needing some scientific background to exploit them. Our objective here is to bridge this gap, by using the data we receive from our MSG-SEVIRI (Meteosat Second Generation – Spinning Enhanced Visible InfraRed Imager) station, by processing them to retrieve accurate characteristics of the surface, and uploading them within 5 minutes of image completion on a dedicated webpage, updated with every new data. For half our planet, we provide in real time a specifically designed quickook and surface temperature every 15 minutes, with an accuracy similar to the one achieved in previous works. We also provide every 15 minutes the hotspots detected using a validated approach. Once a day, we provide vegetation greenness (NDVI – Normalized Difference Vegetation Index) for the 12:00 UTC acquisition, corresponding to the best illumination case, as well as anomalies for NDVI and surface temperature. These parameters are provided freely as full resolution images, readily understandable for the end-user, in three different languages (English, Spanish and French): https://www.uv.es/iplsat. These data, along with short time lapse videos, can be used for educational, scientific and communication purposes.